Climate action and bioeconomy transition: Mainstreaming environmental sustainability in the Post-Malabo Agenda of the Comprehensive Africa Agriculture Development Programme - Ecuru, Julius; Savadogo, Moumini; Araba, Debisi; Deconinck, Koen (AKADEMIYA2063, 2024)
The concepts of the green economy, circular economy, blue economy, and bioeconomy started emerging in response to the multidimensional economic, socioecological, and climate change crises. These concepts are becoming popular in sustainability discussions in policy, scientific research, and business and are expected to promote sustainability through different pathways of transformation. Each of these frameworks offers a comprehensive package of solutions, yet all point toward renewable, bio-based processes and nature-based or nature-friendly solutions (Kirchherr, Reike, and Hekkert 2017; Geissdoerfer et al. 2017; D’Amato and Korhonen 2021). The bioeconomy, which is more focused on biological and nature-based/positive processes, is usually viewed as a more holistic concept that encompasses principles of the green economy, circular economy, and blue economy (Figure 12.1).